Infiltration and stability analysis of gravelly soil slopes under rainfall with the improved green-ampt model - Xiong, Xiaoyu; Wu, Wei; Chen, Jianchun; Guo, Li; Cheng, Zihua (Frontiers in Earth Science, 2025)
Rainfall infiltration is a key cause of slope instability, especially in complex soil-rock mixture slopes with preferential flow paths. The classic Green-Ampt model, widely used in infiltration studies, has limitations in handling air pressure variations near the surface of such slopes, causing errors. This study proposes an improved Green-Ampt model that incorporates atmospheric pressure boundary conditions and adjusts the permeability parameter for soil-rock mixtures. The refined model can analyze wetting front depth under various conditions, including constant pressure with/without ponding and atmospheric pressure effects. Finite element simulations of slopes with different stone contents show that block content significantly controls preferential flow and saturation patterns in heterogeneous media, influencing slope stability. Comparisons between theoretical predictions and numerical results confirm the model’s effectiveness in calculating wetting front variations. This study provides a theoretical method for calculating wetting front depth during infiltration in soil-rock mixture slopes, considering atmospheric pressure variations.